Allelopathic Influence of Acacia holosericea on Annual Crops - Divya, M.P.; Ayyasamy, M.; Bhavanisanker, K. (Indian Journal of Agroforestry, 2020)
A pot culture experiment was conducted with four soil media viz., top soil, rhizosphere soil, soil mulched with dry leaves and ordinary field soil as control. When compared to the ordinary field soil, the other three soil media viz., top soil, rhizosphere soil, soil mulched with dry leaves significantly depressed the growth and yield of four test crops, viz., cowpea, sesame, horse gram and sorghum. Among the different soil media, the maximum suppression in germination was recorded under top soil. The maximum reduction in shoot length, root length (at 40 days after sowing and at harvest) and grain yield was recorded under rhizosphere soil. The highest reduction in the dry matter production (at 40 days after sowing and at harvest) and number of leaves was recorded under soil mulched with dry leaves. The results revealed that Acacia holosericea was having atletopathic effect on the following agricultural crops viz., cowpea, sesame, horse gram and sorghum.